2016
DOI: 10.1007/s13199-016-0425-8
|View full text |Cite
|
Sign up to set email alerts
|

Influence of salt stress on inoculated Casuarina glauca seedlings

Abstract: Salinity is a serious threat to agriculture in arid and semi-arid regions including Egypt. There is currently a need to select highly salt-tolerant plants to improve recycling of agricultural drainage waters. Due to the importance of Casuarina in soil reclamation and rehabilitation, our study was carried out to evaluate the survival and growth of inoculated Casuarina glauca in hydroponic N-free medium supplemented with different NaCl concentrations (50, 100, 200, 300, 400 and 500 mM). Salt tolerant Frankia str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
8
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 28 publications
1
8
0
Order By: Relevance
“…Although we observed the salt stress effects on this solute concentration in roots were significantly more evident than shoots, leaves proline accumulation was considerably higher than in roots. It has been suggested that leaves accumulate more proline to maintain chlorophyll level and cell turgor to protect photosynthetic activity under salt stress (Silva-Ortega et al 2008, Huang et al 2013, Mansour et al 2016. This is consistent with our results indicating that proline accumulation was greatest in the leaves of stressed plants.…”
Section: Osmoregulationsupporting
confidence: 93%
See 1 more Smart Citation
“…Although we observed the salt stress effects on this solute concentration in roots were significantly more evident than shoots, leaves proline accumulation was considerably higher than in roots. It has been suggested that leaves accumulate more proline to maintain chlorophyll level and cell turgor to protect photosynthetic activity under salt stress (Silva-Ortega et al 2008, Huang et al 2013, Mansour et al 2016. This is consistent with our results indicating that proline accumulation was greatest in the leaves of stressed plants.…”
Section: Osmoregulationsupporting
confidence: 93%
“…Salinity can affect plant in a multivariate way, primarily reaching plant growth due to osmotic and ionic components and mineral defi ciency, and following with several metabolic processes as photosynthesis, protein synthesis and lipid metabolism (Praxedes et al 2010, Silva et al 2015, Mansour et al 2016. The control of the absorption of toxic ions by the roots and their transport and distribution through the plant, as well as the capacity to compartmentalize them in the vacuole, has been considered one of the main mechanisms of tolerance to salt stress (Ashraf & Harris 2004, Liang et al 2018.…”
Section: Introductionmentioning
confidence: 99%
“…However, broad, interdisciplinary and integrate research to ascertain the contribution of symbiotic Frankia to the environmental plasticity of actinorhizal species has emerged only recently, mostly focusing on salt stress in Casuarinaceae, particularly in the model species Casuarina glauca Sieb. ex Spreng e.g., Santos et al, Ribeiro et al, Batista-Santos et al, Mansour et al, Ribeiro-Barros et al, Jorge et al, and Ngom et al [2][3][4][5][6][7][8][9]. C. glauca is a tropical tree widely used to prevent desertification and erosion, as well as to rehabilitate poor and degraded soils [1,10].…”
Section: Introductionmentioning
confidence: 99%
“…C. glauca is a tropical tree widely used to prevent desertification and erosion, as well as to rehabilitate poor and degraded soils [1,10]. Such capacity does not necessarily depend on the symbiosis with Frankia, although some strains may enhance stress tolerance [4][5][6]9,[11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…Besides the global contribution of filaos for the rehabilitation of poor sites in various areas of the world such as China and India (Zhang et al 2016) and of alder for the same purpose in Canada (Callender et al 2016), a major focus is the search for salinity-resistant casuarina lineages . The underlying mechanisms are also being studied (Mansour et al 2016;Selvakesavan et al 2016). As pioneer species, actinorhizal plants are exposed to a wide array of stresses (Ngom et al 2016b) which have been reviewed along with approches to transform Casuarina genetically (Froussart et al 2016).…”
mentioning
confidence: 99%